Excipient-Free Inhalable Microparticles of Azithromycin Produced by Electrospray: A Novel Approach to Direct Pulmonary Delivery of Antibiotics - Beatriz Arauzo; Tania B. Lopez-Mendez; Maria Pilar Lobera; Javier Calzada-Funes; Jose Luis Pedraz; Jesus Santamaria (MDPI AG, 2021)
Inhalation therapy offers several advantages in respiratory disease treatment. Azithromycin is a macrolide antibiotic with poor solubility and bioavailability but with a high potential to be used to fight lung infections. The main objective of this study was to generate a new inhalable dry powder azithromycin formulation. To this end, an electrospray was used, yielding a particle size around 2.5 µm, which is considered suitable to achieve total deposition in the respiratory system. The physicochemical properties and morphology of the obtained microparticles were analysed with a battery of characterization techniques. In vitro deposition assays were evaluated after aerosolization of the powder at constant flow rate (100 L/min) and the consideration of the simulation of two different realistic breathing profiles (healthy and chronic obstructive pulmonary disease (COPD) patients) into a next generation impactor (NGI). The formulation was effective in vitro against two types of bacteria, Staphylococcus aureus and Pseudomonas aeruginosa. Finally, the particles were biocompatible, as evidenced by tests on the alveolar cell line (A549) and bronchial cell line (Calu-3).